Social and metabolic mediation of growth performance in a temperate estuarine fish - Hoots, Elizabeth C.; Doling, Juliet Bao Ngoc; Kuchenmüller, Luis L.; Skeeles, Michael R.; Clark, Timothy D. (Frontiers in Fish Science, 2024)
Despite the importance of juvenile growth to lifetime fitness, high variability exists within many fish species where some individuals grow markedly faster than others. Here, we explored whether social context mediated growth performance in n=35 Galaxias maculatus by manipulating the social environment after identifying different growth phenotypes. We found that initially fast-growing fish slowed their growth rate when pooled with similarly fast-growing individuals, whereas none of the initially slow-growing fish markedly improved their growth when pooled with other slow-growers. We examined for any metabolic underpinnings to the findings by measuring standard, routine, and maximum metabolic rates (SMR, RMR and MMR) at two time points separated by ~4 months. SMR and RMR positively correlated with growth rates when the fish were pooled into growth phenotypes, but not when they were returned to their original (mixed) social groups. We highlight research directions to further elucidate how social context and metabolism interact to govern growth phenotype.